Identification of important residues by computational alanine scanning analysis of interaction mechanisms of scFv Anti-p17 complexes based on molecular dynamics simulations - Panthip Tue-Ngeun (2018)
Molecular dynamics simulation (MD) coupled with molecular mechanics generalized Born surface area (MM-GBSA) method were performed to probe the binding mechanisms of single chain Fv fragment with p17 epitopes of HIV-1 protease (scFv anti-p17). The results show that van der Waals and electrostatic energy is a main force of the binding. Computational alanine scanning by substitution of the amino acids in binding to alanine and analysis of structure-affinity relation were used to predict the antibody-antigen binding modes. The important residues locate in the hot spot of the surface between scFv and p17 have been identified. This study can contribute significantly to the designs of the novel antibody targeting the p17 peptides. Point mutations and molecular docking between the modeled scFv antibody and p17 peptides have been investigated in some of the key residues to search for novel antibody with the improved binding activity. The experimental results have been compared to see how well of the prediction. © 2014 Taylor & Francis Group, LLC.